The effects of starting age for volleyball-specific training on long-term outcomes - Rudesill, D. N. (University of Louisiana, 2018)
Many athletes have started to specialize in a particular sport at a much younger age. To narrow down the population we looked into volleyball athletes that sport specialize at a younger age compared to those that wait until a later age. Looking into the long term effects on the athlete`s skill level, injury and burnout rates. This cross-sectional study took two days of data collections involving 27 participants. Testing consisting of sport specific testing, anthropometrics, and surveys to investigate for volleyball history, injury and burnout in participants. Data showed that athletes that have participated for more than 3 years had a higher vertical approach and standing jump. Along with their motor development, the t-test agility test showed they were able to change direction with more ease and at a faster rate than those athletes having played less. The self-reported data showed that athletes had more ankle injuries as compared to others and 12 out of the 18 athletes reported feeling burnout from the year round sport. Concluding that the athletes that start at an earlier age have more increased motor development leading to their ability to move with ease when demonstrating the sport specific skills. More data is needed to come to a conclusion about the injury and burnout rate in the sport-specific athletes.